In Search for a Bourdieusian Approach to “Gentrification”: Looking through the Radiance of Academic Doxa - Šarūnas, Tadas (Socialinė teorija, empirija, politika ir praktika, 2021)
Despite the potential of Pierre Bourdieu’s sociology to advance debates of urban studies, this potential is so far used only superficially. In this article I take arguments from the debate on gentrification as an example to show how Bourdieu’s sociology could help us look through the common sense notions of urban studies. But despite the critique for the debate on gentrification, I argue that we should keep on approaching these empiric locations. They enable us to produce sensitive stories on the effects that social forces have on our everyday lives in cities and – in particular – to show the role that housing policy has in the reproduction of power relations.
Keywords: Bourdieu; gentrification; housing policy; symbolic violence